Primer on Pulsed Electrical Field Ablation - Atul Verma; Samuel J. Asivatham; Thomas Deneke; Quim Castellví; Robert E. Neal (2021)
Pulsed electrical field (PEF) energy is a promising technique for catheter ablation of cardiac arrhythmias. In this article, the key aspects that need to be considered for safe and effective PEF delivery are reviewed, and their impact on clinical feasibility is discussed. The most important benefit of PEF appears to be the ability to kill cells through mechanisms that do not alter stromal proteins, sparing sensitive structures to improve safety, without sacrificing cardiomyocyte ablation efficacy. Many parameters affect PEF treatment outcomes, including pulse intensity, waveform shape, and number of pulses, as well as electrode configuration and geometry. These physical and electrical characteristics must be titrated carefully to balance target tissue effects with collateral implications (muscle contraction, temperature rise, risk of electrical arcing events). It is important to note that any combination of parameters affecting PEF needs to be tested for clinical efficacy and safety. Applying PEF clinically requires knowledge of the fundamentals of this technology to exploit its opportunities and generate viable, durable health improvements for patients.